Multidimensional exploration of essential oils generated via eight oregano cultivars: Compositions, chemodiversities, and antibacterial capacities - Hao, Y.; Kang, J.; Yang, R.; Li, H.; Cui, H.; Bai, H.; Shi, L.
Numerous species of Origanum (Lamiaceae)have been widely used as spices to extend the shelf life of foods. Essential oils extracted from this genus have attracted much attention owing to their potential applications as bactericides. Here, we evaluated the chemical compositions of eight oregano essential oils (OEOs)using gas chromatography-mass spectrometry and assessed their antibacterial activities. The chemical compositions of OEOs were affected by the cultivar factor, and seven common compounds, including carvacrol, were identified among eight OEOs. Partial least squares discriminant analysis enabled the distinction of three groups among these OEOs, as characterized by the proportions of carvacrol, thymol, and sesquiterpenes. OEOs effectively inhibited Escherichia coli and Staphylococcus aureus with varying antibacterial activities. Spearman correlation network highlighted core antibacterial contributors in the chemical profiles of OEOs. Our results revealed that the bacteriostatic effects of OEOs could be explained by core compounds and their synergistic effects.
Keywords: OREGANO ESSENTIAL OIL; CHEMODIVERSITY; CARVACROL; RANDOM FOREST ALGORITHM; PARTIAL LEAST SQUARES DISCRIMINANT ANALYSIS; ANTIBACTERIAL ACTIVITY